PEMANFAATAN LINGKUNGAN SEBAGAI SUMBER BELAJAR PADA PESERTA DIDIK - Rusnawati (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2020)
In learning, the environment becomes a tool or media so that the implementation of learning will be smoother, students will quickly understand, and the learning process is carried out effectively. For that, the teacher must be able to take advantage of the environment as a source of learning for students. The formulation of the problem in this study is what is meant by the environment as a learning resource. What are the types of environments as learning resources. How does the environment function as a learning resource. And how is the use of the environment as a source of learning for students. To be able to find answers to the problems raised, the authors use a qualitative approach. From the research results, it can be concluded that the environment is everything that is around students that affects the development of students' lives, either directly or indirectly. The environment as a learning resource is one of the places and spaces used by the teacher in the process of implementing learning. Environments that can be used as a source of learning include community, natural, biotic and abiotic. Which has psychological, pedagogic and instructional functions. The environment as a learning resource can be done by teachers by presenting, designing, or bringing students through educational facilities and tools. So that the learning process takes place in an interesting, fun way and learners understand faster and learning goals are achieved effectively and efficiently.